Neutron radiation effects on the electrical characteristics of InAs/GaAs quantum dot-in-a-well structures - Ahmad Fauzi, D.; Md Rashid, N. K. A.; Mohamed Zin, M. R.; Hasbullah, Nurul Fadzlin (IEEE, 2015)
This paper studies the effects of neutron radiation on the electrical behaviour and leakage current mec hanism of quantum dot-in-a-well (DWELL) semiconductor diodes with fluence ranging from 3 to neutron/cm . After neutron irradiation, the forward bias and reverse bias le akage currents showed significant rise approximately of up to two orders of magnitude which is believed to be attributed to the presence of displacement damage induced traps. The ideality factor of the forward bias leakage current corresponding to all neutron fluenceirradiationswerefoundtobecloseto2,suggestingthatthe forward bias current mechanism is large ly due to trap-assisted generation-recombination (TAGR )ofcarriers.Subsequently,it is also observed that the capacit ances reduced after irradiations which were further shown to be due to th e deep carrier trapping effects and the Neutron Transmutation Doping effects (NTD). From the temperature dependence measurements, it is found that the reverse bias leakage curren tmechanismsoftheirradiated samplesareprimarilyattributedtotwoprocess;TAGRofcarriers with emission from the traps assisted by the Frenkel-Poole (F-P).The traps due to both mechanis ms were derived and shown to increase with neutron fluence.